2019
DOI: 10.1128/jcm.01975-18
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Microfluidic Assay for Diagnosing Tuberculous Meningitis in HIV-Uninfected Patients

Abstract: We evaluated the diagnostic performance of a simple and label-free pathogen enrichment method using homobifunctional imidoesters (HI) and a microfluidic system, called the SLIM assay, followed by real-time PCR from cerebrospinal fluid (CSF) in human immunodeficiency virus (HIV)-uninfected patients with suspected tuberculous meningitis (TBM). Patients with suspected TBM were prospectively enrolled in a tertiary hospital in an intermediate tuberculosis (TB)-burden country during a 30-month period. TBM was classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In most conventional assays, only a small quantity of clinical sample is used for pathogen detection uses, then the remaining sample unused. However, the SLIM assay uses larger sample volumes (up to 50 mL) with simultaneous pathogen concentration and extraction in a single system [3,4], with comparable time to Xpert MTB/RIF (2.5-4.5 h for SLIM) but with significantly lower cost ($5-6 for SLIM) and instrument requirements for sample processing. In the current study, we showed superior sensitivity of the SLIM assay compared to the Xpert MTB/RIF, especially for detecting smear-negative PTB.…”
Section: Citementioning
confidence: 99%
See 2 more Smart Citations
“…In most conventional assays, only a small quantity of clinical sample is used for pathogen detection uses, then the remaining sample unused. However, the SLIM assay uses larger sample volumes (up to 50 mL) with simultaneous pathogen concentration and extraction in a single system [3,4], with comparable time to Xpert MTB/RIF (2.5-4.5 h for SLIM) but with significantly lower cost ($5-6 for SLIM) and instrument requirements for sample processing. In the current study, we showed superior sensitivity of the SLIM assay compared to the Xpert MTB/RIF, especially for detecting smear-negative PTB.…”
Section: Citementioning
confidence: 99%
“…The specialists choosing TB treatment were blinded to SLIM assay results. SLIM assay principles and detailed methods have been described previously [3,4]. Briefly, a mixture of sputum sample and liquefaction solution with HIs reagent were added to the SLIM system to enrich M. tuberculosis and DNA extracted without the need for detergents or bulky instruments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of the Xpert assay is not high enough for paucibacillary TB cases ( 4 , 12 ), and is thus limited for use in smear-negative TB cases that require more sensitive diagnostic methods. To meet this unmet clinical need, we applied the SLIM assay, a new generation pathogen enriching technique, and demonstrated its efficacy in PTB and other infectious diseases ( 9 , 10 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of GeneXpert, a cartridge based rapid molecular test was still not high enough to rule out TBM (45-67% sensitivity to detect microbiologically proven TBM). GeneXpert Ultra has 70% sensitivity versus clinical case definition and misses up to 30% of cases [5]. However, a recent study from Donovan et al reported that GeneXpert Ultra was not superior to GeneXpert for TBM diagnosis in both HIV-uninfected and HIV-infected adults [6].…”
Section: Introductionmentioning
confidence: 99%